Combined sound conditioning therapy and counseling for tinnitus treatment: proof-of-concept study in Colombia - Ronderos, Angela M.; González, Daniela; García, Alejandro; Barón, Clemencia; García, Juan M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Demonstrate the efficacy and applicability of sound conditioning therapy (SCT) with counseling for tinnitus treatment in subjects with normal hearing and mild-moderate hearing loss using therapeutic frequency modulated noise in a developing country. Retrospective cohort study evaluating 18 patients treated with SCT between 2018 and 2020 in a tertiary-care hospital outpatient tinnitus clinic in Bogotá, Colombia. Tinnitus intensity was quantified in decibels (dB) sound pressure level (SPL) and measured with the visual analogue scale (VAS) before and after treatment with SCT. Quality of life change after the intervention was evaluated with the tinnitus handicap index (THI) and the tinnitus reaction questionnaire (TRQ). Subjects received SCT for 2 to 7 months with two daily customized sound sessions and periodic counseling based on cognitive behavioral therapy (CBT) principles. After treatment there was a significant decrease (p<0.01) for all outcomes measured including a mean difference in tinnitus intensity of 7.6 dB (95% CI, 4.5-10.7), VAS score of 4.5 (95% CI, 3.5-5.5), TRQ score of 36.4 (95% CI, 29.8-43) and THI score of 33.1 (95% CI, 25.6-40.5) compared to baseline. SCT and CBT-based counseling should be available as an alternative in patients with tinnitus treated with a multidisciplinary team. This study shows the improvement in symptoms and quality of life after treatment. Future research is warranted with a larger sample size and longer follow-up periods to show the overall effect of SCT and CBT-based counseling.